# The variables x and y are inversely proportional, and y=2 when x=3 what is the value of y when x=9

QUESTION POSTED AT 03/12/2019 - 10:29 AM

QUESTION POSTED AT 03/12/2019 - 10:29 AM

Inverse proportion:

y=2 when x=3.

y=? when x=9.

y=2/3 when x=9.

y=2 when x=3.

y=? when x=9.

y=2/3 when x=9.

We need to solve the system of equations.

If we solve by graphing, we get the answer:

ANSWERED AT 09/12/2019 - 05:05 AM

QUESTION POSTED AT 09/12/2019 - 05:05 AM

An expression for a type of proportionality so like y=kx where y is dependent and x is independent and the y and x will be the variables while k is constant of proportionality
This can also be stated k=y/x so to find k you divide dependent by independent
Don't confuse this with science trust me you don't wanna do the y/x in science

ANSWERED AT 09/12/2019 - 05:03 AM

QUESTION POSTED AT 09/12/2019 - 05:03 AM

A comparison of two numbers or variables is a proportion

ANSWERED AT 09/12/2019 - 05:01 AM

QUESTION POSTED AT 09/12/2019 - 05:01 AM

Y = (x - 3)² + 53

y = (x - 3)(x - 3) + 53

y = (x(x - 3) - 3(x - 3)) + 53

y = (x(x) - x(3) - 3(x) + 3(3)) + 53

y = x² - 3x - 3x + 9 + 53

y = x² - 6x + 62

y = (x - 3)(x - 3) + 53

y = (x(x - 3) - 3(x - 3)) + 53

y = (x(x) - x(3) - 3(x) + 3(3)) + 53

y = x² - 3x - 3x + 9 + 53

y = x² - 6x + 62

ANSWERED AT 09/12/2019 - 04:45 AM

QUESTION POSTED AT 09/12/2019 - 04:45 AM

43 x 3 tens=

43 × 3= 1290

because you add the 0 because of 3 tens

43 × 3= 1290

because you add the 0 because of 3 tens

ANSWERED AT 09/12/2019 - 04:39 AM

QUESTION POSTED AT 09/12/2019 - 04:39 AM

The answer is 3^12. i'd explain it but i took me seven minutes to do the the problem myself. :)

ANSWERED AT 09/12/2019 - 04:25 AM

QUESTION POSTED AT 09/12/2019 - 04:25 AM

The two answers to this problem is y=-18 and y=14.

ANSWERED AT 09/12/2019 - 04:23 AM

QUESTION POSTED AT 09/12/2019 - 04:23 AM

Ok....so look at the attached picture

ANSWERED AT 09/12/2019 - 02:45 AM

QUESTION POSTED AT 09/12/2019 - 02:45 AM

Its B like terms she can combine are 12 and 3 simply because there are no numbers with -x

ANSWERED AT 09/12/2019 - 02:33 AM

QUESTION POSTED AT 09/12/2019 - 02:33 AM

It is greater to 6 on the number line i did this i got it right

ANSWERED AT 09/12/2019 - 01:31 AM

QUESTION POSTED AT 09/12/2019 - 01:31 AM

The answer is **b** because the 3 is in the x value spot. (x,y)

ANSWERED AT 08/12/2019 - 05:02 PM

QUESTION POSTED AT 08/12/2019 - 05:02 PM

Since the 3 is outside of the parentheses you would have to distribute it. This means that you multiply x by 3, then you multiply 4 by three to get 3(x) + 3(4). SO 3 time x equals 3x plus 3 time 4 equals 12

This would give you 3x+12

This would give you 3x+12

ANSWERED AT 08/12/2019 - 04:41 PM

QUESTION POSTED AT 08/12/2019 - 04:41 PM

Wouldn't this be the answer? The answer is 40nickels/standard coin? I actually researched this myself for you and that's the answer that came up, so sorry if this is incorrect

Hope I helped! :)

ANSWERED AT 08/12/2019 - 04:34 PM

QUESTION POSTED AT 08/12/2019 - 04:34 PM

A horizontal line would be parallel to the x-axis. This means that it would be in the form y= ____. Because coordinates of a point are written as (x,y) the corresponding y coordinate for this horizontal line would be 4.

The final answer is C. y=4

The final answer is C. y=4

ANSWERED AT 08/12/2019 - 04:29 PM

QUESTION POSTED AT 08/12/2019 - 04:29 PM

No because no matter what u multiply 7:5 u will never get 35:10, they are not equal

ANSWERED AT 08/12/2019 - 04:22 PM

QUESTION POSTED AT 08/12/2019 - 04:22 PM

To factor an expression, first you have to find the GCF or Greatest Common Factor of all of the pieces of the expression.

The GCF of 2y^2 and -4y is 2y

So, to factor this expression, we need to divide all of the pieces of the expression by the GCF.

2y(y-2)

2y^2 - 4y in completely factored form is 2y(y-2)

The GCF of 2y^2 and -4y is 2y

So, to factor this expression, we need to divide all of the pieces of the expression by the GCF.

2y(y-2)

2y^2 - 4y in completely factored form is 2y(y-2)

ANSWERED AT 08/12/2019 - 04:18 PM

QUESTION POSTED AT 08/12/2019 - 04:18 PM

Y-y1= m(x1-x2)

using this formula

the answer is d

because slope has to remain the same if its parallel

using this formula

the answer is d

because slope has to remain the same if its parallel

ANSWERED AT 08/12/2019 - 04:16 PM

QUESTION POSTED AT 08/12/2019 - 04:16 PM

Well if 9 x 3 = 27 then its just 27 %

ANSWERED AT 08/12/2019 - 04:12 PM

QUESTION POSTED AT 08/12/2019 - 04:12 PM

f(x) = -5x^2 - x + 20;

f(3) = -5*3^2 - 3 + 20 = -5*9 - 3 + 20 = -45 - 3 + 20 = -28;

ANSWERED AT 08/12/2019 - 04:05 PM

QUESTION POSTED AT 08/12/2019 - 04:05 PM

7x+8x+2=18x-27-8

(you remove the paranthesys, then take all X's in one side and the other numbers in the other side)

3x=33

x=11

(you remove the paranthesys, then take all X's in one side and the other numbers in the other side)

3x=33

x=11

ANSWERED AT 08/12/2019 - 03:57 PM

QUESTION POSTED AT 08/12/2019 - 03:57 PM

-2+2=2(-1-d)

0=2(-1-d)

0=-2-2d

2=-2d

-1=d

4+2=2(2-d)

6=2(2-d)

6=4-2d

2=-2d

-1=d

so the answer for d would be -1, I substituted the coordinates of x and y with the points to get the answer

0=2(-1-d)

0=-2-2d

2=-2d

-1=d

4+2=2(2-d)

6=2(2-d)

6=4-2d

2=-2d

-1=d

so the answer for d would be -1, I substituted the coordinates of x and y with the points to get the answer

ANSWERED AT 08/12/2019 - 03:41 PM

QUESTION POSTED AT 08/12/2019 - 03:41 PM

X=13 that is what I got

ANSWERED AT 08/12/2019 - 03:34 PM

QUESTION POSTED AT 08/12/2019 - 03:34 PM

Strange as it may seem, I'd need to see exercise 5 before I could even begin to answer that.

ANSWERED AT 08/12/2019 - 02:41 PM

QUESTION POSTED AT 08/12/2019 - 02:41 PM

35 is the answer :D have fun getting cheats on ur hw

ANSWERED AT 08/12/2019 - 02:03 PM

QUESTION POSTED AT 08/12/2019 - 02:03 PM

Y - y₁ = m(x - x₁)

y - 2 = 3(x - 3)

y - 2 = 3(x) - 3(3)

y - 2 = 3x - 9

+ 2 + 2

y = 3x - 7

y - 2 = 3(x - 3)

y - 2 = 3(x) - 3(3)

y - 2 = 3x - 9

+ 2 + 2

y = 3x - 7

ANSWERED AT 08/12/2019 - 01:38 PM

QUESTION POSTED AT 08/12/2019 - 01:38 PM

First you have to distribute the negative(=-1) with the numbers in the parentheses.

-1×9=-:

-1×-3x=3x

You now have:

4x-9+3x=8x-1

Now combine like terms:

4x+3x=7x

Now you have:

7x-9=8x-1

Now isolate that x:

7x-8x=-x

-1+9=8

You now have:

-x=8

Divide by -1 and get:

x=-8

-1×9=-:

-1×-3x=3x

You now have:

4x-9+3x=8x-1

Now combine like terms:

4x+3x=7x

Now you have:

7x-9=8x-1

Now isolate that x:

7x-8x=-x

-1+9=8

You now have:

-x=8

Divide by -1 and get:

x=-8

ANSWERED AT 08/12/2019 - 01:28 PM

QUESTION POSTED AT 08/12/2019 - 01:28 PM

You can write them as fractions, reduce them, then compare them.

ANSWERED AT 08/12/2019 - 01:12 PM

QUESTION POSTED AT 08/12/2019 - 01:12 PM

Answer

The equation represented the proportional relationship between the wages she earns (w) and the number of hours (h) .

w=52h

**Reason**

As given

Maya is interning at a law firm over the summer and is paid by the hour.

If her hourly wage is $52

w = wages maya earns

h = number of hours

Than the equation becomes in the form

w = 52× h

**w = 52h**

**Therefore the wages maya earns is represented by** **w = 52h .**

ANSWERED AT 08/12/2019 - 01:00 PM

QUESTION POSTED AT 08/12/2019 - 01:00 PM

D. y = 4/5x - 9/5

ANSWERED AT 08/12/2019 - 12:40 PM

QUESTION POSTED AT 08/12/2019 - 12:40 PM